Indonesia's Middle-Power Diplomacy amid U.S.–China Strategic Competition: Domestic Politics and Foreign Policy Transformation - Putri Azzahra Nirmala (Indonesian Political Transformation, 2026)
The intensifying strategic rivalry between the United States and China has fundamentally reshaped the geopolitical landscape of the Indo-Pacific, placing middle powers under increasing pressure to navigate competing political, economic, and security interests. Indonesia has responded by reinforcing its long-standing "free and active" foreign policy while simultaneously expanding economic cooperation with China and strengthening strategic partnerships with the United States and other regional actors. Despite growing scholarly attention to Indonesia's external balancing strategy, limited research has examined how domestic political dynamics influence its evolving diplomatic posture. This study investigates the interaction between domestic political transformation and Indonesia's middle-power diplomacy amid great-power competition. Employing a qualitative research design, the study combines foreign policy analysis, elite interviews, parliamentary debates, and official policy documents to examine decision-making processes between 2019 and 2025. The findings indicate that Indonesia's diplomatic flexibility is shaped not only by geopolitical considerations but also by domestic economic priorities, leadership preferences, bureaucratic coordination, and public perceptions of national sovereignty. Rather than adopting a traditional balancing or bandwagoning strategy, Indonesia has developed a multidimensional diplomatic approach that seeks strategic autonomy through diversified partnerships, regional leadership within ASEAN, and issue-based cooperation. The article contributes to international relations scholarship by integrating domestic political variables into the analysis of middle-power diplomacy in the Global South. It further argues that Indonesia's foreign policy transformation demonstrates how emerging democracies can preserve policy independence while responding to structural changes in the international system. The study offers broader implications for understanding strategic autonomy among middle powers confronting increasingly polarized global politics.